Review article: current and future treatment approaches for pain in IBS. (19th December 2021) - Paine, Peter
Summary: Background: Abdominal pain is a core symptom of IBS and a primary driver of care seeking. Visceral hypersensitivity is a key pathophysiological mechanism and therapeutic target for pain in IBS, with components of peripheral and central sensitisation and psychological factors. Aim: To review current and future treatment approaches specifically for the pain component of IBS. Methods: Pubmed search terms included combinations of irritable bowel, pain, visceral hypersensitivity, novel, new, emerging, future and advances. Results: Established non‐pharmacological treatments for IBS pain include the low FODMAP diet, probiotics and psychological interventions, especially hypnotherapy. Tricyclics remain the best evidenced pharmacological approach with GCC agonists, tenapanor, lubiprostone, eluxadoline and 5HT3 antagonists second line according to patient characteristics and availability. Less well‐evidenced current options include anti‐spasmodics, peppermint oil, SSRIs, SNRIs, alpha 2 delta ligands, melatonin and histamine antagonists. Patients are vulnerable to iatrogenesis and harmful approaches to be avoided include opioids and unwarranted surgical interventions. For severe pain, the concept of augmentation with combined gut‐brain neuromodulators and psychotherapy in a multi‐disciplinary setting is considered. A plethora of molecular targets and ligands are emerging from pre‐clinical studies, together with early clinical evidence for a range of pharmacological, dietary, neurostimulation and novel psychological treatment delivery methods which are reviewed. The history of such emerging approaches, however, merits both caution and optimism in equal measure. Conclusions: Despite good in‐roads and emerging options, the management of abdominal pain remains one of the biggest challenges and research priorities for patients with IBS.